The handbook for standardized field and laboratory measurements in terrestrial climate change experiments and observational studies (ClimEx). Issue 1 (9th December 2019) - Halbritter, Aud H.; De Boeck, Hans J.; Eycott, Amy E.; Reinsch, Sabine; Robinson, David A.; Vicca, Sara; Berauer, Bernd; Christiansen, Casper T.; Estiarte, Marc; Grünzweig, José M.; Gya, Ragnhild; Hansen, Karin; et al.
Abstract: Climate change is a world‐wide threat to biodiversity and ecosystem structure, functioning and services. To understand the underlying drivers and mechanisms, and to predict the consequences for nature and people, we urgently need better understanding of the direction and magnitude of climate change impacts across the soil–plant–atmosphere continuum. An increasing number of climate change studies are creating new opportunities for meaningful and high‐quality generalizations and improved process understanding. However, significant challenges exist related to data availability and/or compatibility across studies, compromising opportunities for data re‐use, synthesis and upscaling. Many of these challenges relate to a lack of an established 'best practice' for measuring key impacts and responses. This restrains our current understanding of complex processes and mechanisms in terrestrial ecosystems related to climate change. To overcome these challenges, we collected best‐practice methods emerging from major ecological research networks and experiments, as synthesized by 115 experts from across a wide range of scientific disciplines. Our handbook contains guidance on the selection of response variables for different purposes, protocols for standardized measurements of 66 such response variables and advice on data management. Specifically, we recommend a minimum subset of variables that should be collected in all climate change studies to allow data re‐use and synthesis, and give guidance on additional variables critical for different types of synthesis and upscaling. The goal of this community effort is to facilitate awareness of the importance and broader application of standardized methods to promote data re‐use, availability, compatibility and transparency. We envision improved research practices that will increase returns on investments in individual research projects, facilitate second‐order research outputs and create opportunities for collaboration across scientific communities. Ultimately, this should significantly improve the quality and impact of the science, which is required to fulfil society's needs in a changing world. RESUMEN: El cambio climático es una amenaza global para la biodiversidad, la estructura y funcionamiento de los ecosistemas y la habilidad de éstos para generar servicios ecosistémicos. Para poder comprender las causas y los mecanismos subyacentes, y poder predecir las consecuencias del cambio climático tanto para la naturaleza como para los seres humanos, debemos entender la magnitud y dirección de estos cambios a través del continuo suelo‐planta‐atmósfera. El creciente número de estudios sobre cambio climático brinda nuevas oportunidades para poder generalizar de forma más robusta y entender mejor los procesos implicados. Sin embargo, todavía hay grandes obstáculos en cuanto a la disponibilidad de datos y cómo de compatibles son los distintos estudios, que ponen en riesgo las oportunidades para reutilizar y sintetizar datos y comparar a distintas escalas. Estos obstáculos limitan nuesta habilidad para comprender los complejos procesos y mecanismos relacionados con el cambio climático en ecosistemas terrestres. Para superar estos obstáculos, hemos recopilado recomendaciones metodológicas basadas en las mejores prácticas propuestas por las principales redes de investigación en ecología, avalados por 115 expertos de un amplio rango de disciplinas científicas. Nuestro manual contiene recomendaciones para la selección de variables respuesta para diferentes propósitos, y protocolos para realizar medidas estandarizadas de 66 posibles variables respuesta, así como sugerencias para la gestión de los datos obtenidos. Recomendamos específicamente un mínimo de variables que deben medirse en todos los estudios sobre cambio climático para permitir la reutilización y síntesis de datos. Además, sugerimos una serie de variables adicionales que pueden ser relevantes para distintos tipos de síntesis y para la comparación a distintas escalas. El objetivo de este esfuerzo comunitario es concienciar sobre la importancia de la aplicación de métodos estandarizados para facilitar la reutilización, disponibilidad, compatibilidad y transparencia de los datos. Mejorar las prácticas de investigación aumentará la eficiencia de proyectos de investigación individuales, facilitará resultados de investigación de segundo orden y creará oportunidades para la colaboración entre comunidades científicas. Por último, estas prácticas mejorarán considerablemente la calidad y el impacto de la ciencia, que se requiere para satisfacer las necesidades de la sociedad en un mundo cambiante. 摘要: 气候变化正在对全球生物多样性, 生态系统结构, 功能和服务造成严重的威胁。为了理解这一过程的潜在驱动和机制, 以及预测这一过程对自然和人类社会的影响, 我们迫切的需要更好的了解气候变化对土壤‐植物‐大气系统影响的方向和强度。不断增加的相关方向的研究正在使对该研究领域的数据进行广泛而有意义的概括和总结成为可能, 从而进一步提高我们对这一重要过程的理解。然而, 显著的挑战依然存在, 特别是不同的生态研究产生的数据的可获得性和兼容性有着巨大差异, 这在一定程度上限制了研究数据的再度利用, 概括总结以及进一步推广应用。这个挑战与我们在观测气候变化和生态系统的关键影响及响应时缺乏良好的"最佳实践"有关。这个问题在很大程度上限制了我们对气候变化背景下陆地生态系统的复杂过程和机制的理解。 为了克服这些挑战, 我们收集了基于115个不同陆地生态研究领域的专家总结的主要生态研究网络和试验中的"最佳实践"方法。我们建立的"最佳实践"手册包括了对不同研究目的下选择测量的生态响应变量的建议, 测量66个生态响应变量的标准化流程, 以及如何进行数据管理的建议。特别地, 为了达到研究数据的可再度利用和融合, 我们推荐了一个在所有相关陆地生态研究中必须收集的最小数据集。同时针对不同类型的数据融合和推广应用, 我们给出了额外的关键数据和变量的收集建议。我们的工作希望能够有助于提高该研究领域的研究者对数据标准化的重要性和广泛应用的认识, 从而促进数据的再度利用, 数据的可获得性, 兼容性和透明度。我们期望改进的研究实践将能够增加每一个研究项目的投资回报率, 促进科研数据的二度产出, 以及创造更多的跨研究领域, 跨学科的合作机会。并最终, 显著提高我们的科学研究的质量和影响力, 以满足全球变化下社会对相关科学成果的需求。